2015
DOI: 10.1007/s00270-015-1141-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on MR-Guided High-Intensity Focused Ultrasound Ablation of Sciatic Nerve in a Swine Model: Preliminary Results

Abstract: Introduction Spastic patients often seek neurolysis, the permanent destruction of the sciatic nerve, for better pain management. MRI-guided High Intensity Focused Ultrasound (MRgHIFU) may serve as a noninvasive alternative to the prevailing, more intrusive techniques. This in vivo acute study is aimed at performing sciatic nerve neurolysis using a clinical MRgHIFU system. Methods The HIFU ablation of sciatic nerves was performed in swine (n=5) using a HIFU system integrated with a 3 T MRI scanner. Acute lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
5
6
0
Order By: Relevance
“…myelin disruption and axon swelling) following their highest US-guided HIFU exposures. They are also in agreement with the recent work of Kaye et al [ 32 ], nerve targeting was achieved by identifying a target location with respect to adjacent fat and bony anatomy on T2-weighted fast spin-echo images, as opposed to direct visualization with background-suppressed MR neurography. One benefit of direct visualization of nerves compared to the use of anatomical landmarks was the ability to target smaller areas for ablation (approximately 0.5–1.1cm 2 in our study vs. 4–5 cm 2 in Kaye et al [ 32 ]).…”
Section: Discussionsupporting
confidence: 91%
“…myelin disruption and axon swelling) following their highest US-guided HIFU exposures. They are also in agreement with the recent work of Kaye et al [ 32 ], nerve targeting was achieved by identifying a target location with respect to adjacent fat and bony anatomy on T2-weighted fast spin-echo images, as opposed to direct visualization with background-suppressed MR neurography. One benefit of direct visualization of nerves compared to the use of anatomical landmarks was the ability to target smaller areas for ablation (approximately 0.5–1.1cm 2 in our study vs. 4–5 cm 2 in Kaye et al [ 32 ]).…”
Section: Discussionsupporting
confidence: 91%
“…The MB nerve exhibited nuclear pyknosis of Schwann cells and dilated myelin sheaths, which is consistent with prior studies of FUS ablation of the sciatic nerve in acute rabbit and swine models [8, 11]. Forty-eight-hour survival post-treatment provided time for macrophages and hemorrhage changes to evolve at the boundary of the lesion, which helped clearly delineate the extent of FUS penetration into the spine.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, multiple research studies have focused on the ability of FUS to disrupt nerve conduction and cause necrosis of nerves [8, 9], including MRgFUS renal sympathetic denervation [10], abltation of sciatic [11, 12] and intercostal [13] nerves.…”
Section: Introductionmentioning
confidence: 99%
“…However, the unique properties of bone indicate 1–2 postsonication images may be insufficient to capture the complete dose. Underprediction of thermal dose may account for the discrepancy between thermal dose and contrast‐enhanced imaging showing posttreatment nonperfused volume (NPV) reported in treatments near bone . Indeed, a preclinical study revealed that the ablation zone reached as far as 4 cm beyond the bone target with bone absorption, perfusion, angle of incidence, and shear waves playing a role in the extent of thermal dose in tissue adjacent to bone .…”
mentioning
confidence: 99%
“…Underprediction of thermal dose may account for the discrepancy between thermal dose and contrastenhanced imaging showing posttreatment nonperfused volume (NPV) reported in treatments near bone. 14,23,24 Indeed, a preclinical study revealed that the ablation zone reached as far as 4 cm beyond the bone target with bone absorption, perfusion, angle of incidence, and shear waves playing a role in the extent of thermal dose in tissue adjacent to bone. 13 Figure 1 shows an example of our experience, where after MRgFUS treatment of a metastasis in the left iliac bone, the posttreatment nonperfused area extends 2 cm beyond the bone target, through the muscle tissue and into the fat layer, well beyond the prediction of lethal thermal dose ( Fig.…”
mentioning
confidence: 99%